The Blue Economy and the United Nation’ Sustainable Development Goals: Challenges and Opportunities - Khalil, Saida; Hasanova, Shovkat (Dunakavics, 2024)
The Blue Economy concept, increasingly in vogue, addresses strategic approaches to conserving the planet’s water bodies and oceans. It recognizes the delicate balance between advancing development, progress, and preserving oceanic resources. Its primary goal is to capitalize on opportunities within oceanic economies while responsibly managing potential risks. This discourse underscores the imperative of meeting present-day demands without jeopardizing the requirements of future generations, rooted in the principles of sustainable development. Research endeavors in this realm seek to illuminate prevalent challenges within the Blue Economy domain and devise remedies aligned with the United Nations’ Sustainable Development Goals (SDGs). By identifying and addressing pressing issues, such as overfishing, pollution, and habitat destruction, stakeholders aim to foster a harmonious relationship between economic growth and environmental stewardship. Through innovative strategies and collaborative efforts, the aim is to pave the way for a more sustainable and resilient future, where the oceans can thrive alongside human prosperity.